-3(4X-3)=-12x+13

Simple and best practice solution for -3(4X-3)=-12x+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4X-3)=-12x+13 equation:


Simplifying
-3(4X + -3) = -12x + 13

Reorder the terms:
-3(-3 + 4X) = -12x + 13
(-3 * -3 + 4X * -3) = -12x + 13
(9 + -12X) = -12x + 13

Reorder the terms:
9 + -12X = 13 + -12x

Solving
9 + -12X = 13 + -12x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -12X = 13 + -9 + -12x

Combine like terms: 9 + -9 = 0
0 + -12X = 13 + -9 + -12x
-12X = 13 + -9 + -12x

Combine like terms: 13 + -9 = 4
-12X = 4 + -12x

Divide each side by '-12'.
X = -0.3333333333 + x

Simplifying
X = -0.3333333333 + x

See similar equations:

| -5x-6+9=19 | | 0=8/12y-40 | | 7x-2=(x+1) | | -2x-8+6=7-4x-x | | -1(h+13)=5 | | 49-5=2a-3 | | 2(x-2)=-5 | | 2+4+3x=18 | | 14-(2c+5)=-7c+29 | | 5(2x-3)-x+8=13 | | 33=528x | | 10x+10 = +9x+15 | | X+4=-2-5x | | -2(x-4)=22 | | 7+4(7+4-25)= | | 4h+1+12h=36 | | 3x+57=7x+9 | | -(8y+1)-(-7y-3)=2 | | 15-29=2(x-3) | | 7+s^2(t+4-5r)= | | 5a+8+(-2)=-7 | | -(8y+1)-(-7y-3)=3 | | -(6y+4)-(-5y-6)=5 | | 100(z+3)-3(z-1)=4(z-3)+(z-1) | | y=2(-3) | | 11x=9x+6 | | 3x+10=8x-7 | | b=2f+8 | | 3(-3y+8)=-(-9y+120) | | 4m+18+4m=-20-42-2m | | 35(x+6)=35x-10 | | 1=5x+2 |

Equations solver categories